Nonlinear effects generation in suspended core chalcogenide fibre - El-Amraoui, M.; Duhant, M.; Desevedavy, F.; Renard, W.; Canat, G.; Gadret, G.; Jules, J. C.; Fatome, J.; Kibler, B.; Renversez, G.; Troles, J.; Brilland, L.; et al. (SPIE, the international society for optics and photonics, 2011)
In this work we report our achievements in the elaboration and optical characterizations of low-losses suspended core optical fibers elaborated from As2S3 glass. For preforms elaboration, alternatively to other processes like the stack and draw or extrusion, we use a process based on mechanical drilling. The drawing of these drilled performs into fibers allows reaching a suspended core geometry, in which a 2 μm diameter core is linked to the fiber clad region by three supporting struts. The different fibers that have been drawn show losses close to 0.9 dB/m at 1.55 μm. The suspended core waveguide geometry has also an efficient influence on the chromatic dispersion and allows its management. Indeed, the zero dispersion wavelength, which is around 5 μm in the bulk glass, is calculated to be shifted towards around 2μm in our suspended core fibers. In order to qualify their nonlinearity we have pumped them at 1.995 μm with the help of a fibered ns source. We have observed a strong non linear response with evidence of spontaneous Raman scattering and strong spectral broadening. © 2011 SPIE.
Keywords: Chalcogenide glasses; Fiber; Nonlinear optics; Bulk glass; Chalcogenide glass; Mechanical drilling; Non-linear response; Non-Linearity; Nonlinear effect; Optical characterization; Spectral broadening; Spontaneous Raman scattering; Waveguide geometry; Zero-dispersion wavelength; Crystal whiskers; Dispersion (waves); Glass; Optical sensors; Phase change memory; Photonic crystal fibers; Photonic crystals; Fibers